A A Photovoice Study on Teacher's Emotional Experiences and Challenges in Applying the Dictogloss Technique for Teaching Listening - Khulia Safitri; Afifah Linda Sari; Raida Asfihana (SALEE, 2024)
The challenge in applying a learning technique must be one of the difficulties faced by the teacher in teaching English as a foreign language. This study’s aim is to discover the teacher's emotional experiences and challenges in applying the Dictogloss technique for listening class. The PhotoVoice method was used in this study as the research design. The research regarding the challenges and emotions of teachers in implementing the dictogloss technique for teaching listening has not been carried out much by other researchers, especially using the photovoice research design. The data in this research were analyzed using thematic analysis based on Braun and Clarkes. Based on the findings of this study, the participant has an average positive emotional experience. Furthermore, the results of this study indicate that there are a variety of difficulties in implementing each stage of the Dictogloss technique in teaching listening.